Sustainable Waste Management through Material Flow Analysis and Waste Diversion Rate: A Case Study of Sekolah Alam Bogor, Indonesia - Nur Fitri Hasanah; Eko Ruddy Cahyadi; Mimin Aminah (CV FOUNDAE, 2026)
Sekolah Alam Bogor (Bogor Nature School) provides a relevant case for examining school-based circular waste management in Indonesia. Although the school applies reduce, reuse, and recycle (3R) principles, their implementation remains suboptimal due to the absence of systematic flow mapping and quantitative evaluation. This study aims to quantify waste generation and composition, map material flows, and evaluate the Waste Diversion Rate (WDR) of the school’s circular waste management system. A mixed-method case study was applied, combining field observation, in-depth interviews, and direct weighing of waste over 14 effective school days across five source units: Pre-School, Elementary School, School Kitchen, Middle School, and School of Makers, The results show an average waste generation of 165.15 kg/day, dominated by organic waste (71.23%), with inorganic waste accounting for 28.77%. Salam Permaculture composts organic waste, recyclables are channeled to Bank Sampah Salam Aid, and residues are incinerated. The system achieved an internal Waste Diversion Rate (WDR) of 76% (77.79% when community-contributed recyclables from the Dropzone program are included), indicating substantial waste diversion. However, approximately 24% of the waste (39.70 kg/day) remains as residue treated through incineration, whose emissions and ash quality were not assessed and require further evaluation. These findings indicate that systematic flow mapping and data-driven evaluation are essential for strengthening source-based waste management in educational institutions.